Mass and stiffness spectrometry of nanoparticles and whole intact bacteria by multimode nanomechanical resonators - O. Malvar (Nature Portfolio, 2016)
Mass spectrometry can accurately identify species by molecular mass, but measuring large species can be difficult. Here the authors show that nanomechanical resonators can identify both the mass and stiffness of larger analytes, demonstrating it for gold nanoparticles and E. Colibacteria.